l+.5(3)=.75(l+3)

Simple and best practice solution for l+.5(3)=.75(l+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for l+.5(3)=.75(l+3) equation:


Simplifying
l + 0.5(3) = 0.75(l + 3)

Multiply 0.5 * 3
l + 1.5 = 0.75(l + 3)

Reorder the terms:
1.5 + l = 0.75(l + 3)

Reorder the terms:
1.5 + l = 0.75(3 + l)
1.5 + l = (3 * 0.75 + l * 0.75)
1.5 + l = (2.25 + 0.75l)

Solving
1.5 + l = 2.25 + 0.75l

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-0.75l' to each side of the equation.
1.5 + l + -0.75l = 2.25 + 0.75l + -0.75l

Combine like terms: l + -0.75l = 0.25l
1.5 + 0.25l = 2.25 + 0.75l + -0.75l

Combine like terms: 0.75l + -0.75l = 0.00
1.5 + 0.25l = 2.25 + 0.00
1.5 + 0.25l = 2.25

Add '-1.5' to each side of the equation.
1.5 + -1.5 + 0.25l = 2.25 + -1.5

Combine like terms: 1.5 + -1.5 = 0.0
0.0 + 0.25l = 2.25 + -1.5
0.25l = 2.25 + -1.5

Combine like terms: 2.25 + -1.5 = 0.75
0.25l = 0.75

Divide each side by '0.25'.
l = 3

Simplifying
l = 3

See similar equations:

| y^2-y-72=0 | | 13n-17=2n+10 | | 4(9+x)=120 | | 2x^2-12x=32 | | 8x^3+20x^2+12x=0 | | -2x=2x^2-24 | | 7x=5x+18 | | 4y^2-12y+9=0 | | 5n-23=37 | | 3y^2-y-4=0 | | 2x^2-12=32 | | 60x^2-130x+60=0 | | 23+6q=53 | | 2m+13=3m-7 | | 2(4)=3(10)z+2 | | 3x^2+x=0 | | 5x+9=7x+5 | | x^4-29x^2=-100 | | X^3+4x^2+6x=0 | | 20x-10=4x+54 | | 6x-3y=9 | | 6=0.24x | | 12(x+8)=48(x+2) | | 3x^3-6x^2-72x=0 | | x^5-81x^4=0 | | X^2-18x*81=0 | | 5x*2+10x+5=0 | | 25x^3+20x^2+3x=0 | | 2x^3-6x^2+2x=0 | | 6x^4-10x^3-6x^2=0 | | 4x^3+8x^2-3x=6 | | 8x^2+44x+60=0 |

Equations solver categories